Determinants of retirement planning among employees of manufacturing sector in Shah Alam / Muhammad Azfar Nor Azman - Nor Azman, Muhammad Azfar (Faculty of Business and Management, 2018)
Retirement is the last phase for one's career path. It is a preparation for life without a regular income from work. Thus, the need for retirement income creates a need for retirement planning. Retirement has brought issues related to insufficient funds in funding the expenses of fellow retirees upon retirement. Assumptions or factors was made leading to the necessity of retirement plans. The purpose of this study is to identify the deterrninants of retirement planning among employees of manufacturing sector in Shah Alam. This study applies quantitative approach as questionnaires is the main instruments for data collection. Data were collected from 100 employees from a few selected factories in Shah Alam. Data collected were analysed using descriptive analysis. Various factors were found become as a determinant of retirement planning among employees of manufacturing sector in Shah Alam which are wages, availability of income sources and potential resources, attitude towards money and physical health. From the findings it can determined that only physical health is not become determinant of retirement planning and the wages, availability of income sources and potential resources and attitude towards money become determinant of retirement planning among employees of manufacturing sector in Shah Alam. Overall, this study exposes some information on the awareness towards private retirement scheme among private sector employees in Malaysia and factors influencing their intention for retirement planning.